Understanding Bluetooth Device Security: Is Hacking Possible? - Mitesh G Patel (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In today's digital age, Bluetooth technology is embedded in nearly every device we rely on, from wireless headsets and keyboards to cars and smart home gadgets. While this technology offers great convenience, it also introduces significant risks related to privacy and security. Every Bluetooth-enabled device has its own set of vulnerabilities that cybercriminals may exploit. Raising awareness about these potential threats, as well as how to prevent them, is essential. This article delves into the hidden dangers of Bluetooth technology, illustrating how hackers can bypass advanced security features on devices like laptops, smartphones, cars, and smart home systems to access personal data. Whether you're an everyday user of Bluetooth or a business owner managing multiple devices, understanding these risks is vital to safeguarding your information. The article starts by covering the fundamentals of Bluetooth technology and its operation. It then outlines the security risks associated with using Bluetooth and concludes with practical tips to secure devices and protect sensitive data. DOI: https://doi.org/10.17762/ijisae.v12i3.7615